(untitled) (Journal of Parents and Teachers, 2024)
The article is about a man who was trying to quite smoking and succeeded thanks to the support of his wife and children. Additionally, throughout the pages, it discusses the myths about tobacco and family-related topics concerning smoking and ex-smokers.